1977
DOI: 10.1099/00221287-100-2-395
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium sporogenes Isolates and their Relationship to C. botulinum based on Deoxyribonucleic Acid Reassociation

Abstract: S U M M A R YSixty-two isolates of Clostridium sporogenes from canned foods were examined for cultural properties, heat resistance and DNA-DNA homology to Clostridium botulinum type ~1 9 0 .Sporulation was observed in most of 2 1 umbonate and rhizoidal colony-forming strains (colony-type I strains), but not in most of the 41 strains with convex and circular or crenate colonies with a mat to semi-glossy surface (colony-type I1 strains). More than half of the latter strains showed much higher heat resistance tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…The digestion profile for DpnII demonstrated that C. sporogenes was segregated into two separate populations, one of which showed exact homology with C. botulinum while the other was distinct from all other Clostridium species. These data, along with variations in DNA-DNA hybridization among different strains of C. sporogenes compared to C. botulinum (4,5), suggest that C. sporogenes may be polyphyletic.…”
Section: Discussionmentioning
confidence: 93%
“…The digestion profile for DpnII demonstrated that C. sporogenes was segregated into two separate populations, one of which showed exact homology with C. botulinum while the other was distinct from all other Clostridium species. These data, along with variations in DNA-DNA hybridization among different strains of C. sporogenes compared to C. botulinum (4,5), suggest that C. sporogenes may be polyphyletic.…”
Section: Discussionmentioning
confidence: 93%
“…The similarity between C. botulinum type B (ATCC 25765) and C. botulinum-like strain AIP 355.02 reached the level of 93%. The high percentage of similarity between C. botulinum and C. botulinum-like strains was also mentioned by Nakamura et al (1977), Lee and Riemann (1970). They found that homology between this kind of strain sequences was more than 70%.…”
Section: Discussionmentioning
confidence: 77%
“…Clostridium hastiforme is another nontoxigenic species that is phenotypically similar to C. subterminale, except that it may be less proteolytic, does not produce hydrogen, and produces terminal rather than subterminal spores (4). Genetic relatedness among toxigenic strains of C. botulinum groups I through 111 and their nontoxigenic counterparts has been studied previously (12,13,20,21,25), but similar studies to compare C. botulinum toxin type G, C. subterminale, and C. hastiforme have not been done.…”
mentioning
confidence: 99%